Peanut gastrointestinal delivery oral immunotherapy in adolescents: Results of the build‐up phase of a randomized, double‐blind, placebo‐controlled trial (PITA study). Issue 7 (29th May 2018) - Fauquert, J.‐L.; Michaud, E.; Pereira, B.; Bernard, L.; Gourdon‐Dubois, N.; Rouzaire, P.‐O.; Rochette, E.; Merlin, E.; Evrard, B.; ,
Summary: Background: Oral immunotherapy to peanut is effective in desensitizing patients but has significant side effects including anaphylaxis and gastrointestinal symptoms. In most protocols, peanut is administered in a vehicle food. Objective: In an exclusively adolescent population, we tested a new approach using sealed capsules of peanut (gastrointestinal delivery oral immunotherapy or GIDOIT) to bypass the upper gastrointestinal tract. The primary aim was to assess the efficacy of the oral build‐up phase of GIDOIT and the secondary aim to analyse its safety. Methods: Adolescents with a history of a clinical allergic reaction after peanut ingestion were included in a 2‐armed, parallel‐design, individually randomized, double‐blind, placebo‐controlled, multicentre trial after a positive double‐blind placebo‐controlled oral food challenge (DBPCFC1). A central randomization centre used computer‐generated tables to allocate treatments. Peanut (or placebo) capsules were ingested daily over a period of 24 weeks with increments every 2 weeks from 2 to 400 mg of peanut protein (pp). Primary outcome was tolerance of 400 mg of pp at DBPCFC2. Results: Thirty patients were included between September 2013 and May 2014. At DBPCFC2, unresponsiveness to 400 mg of pp was achieved in 17/21 peanut group patients (2 withdrawn patients) and 1/9 in the placebo group (Intention‐to‐treat analysis, P  < .001, absolute difference = 0.7, 95%IC 0.43 0.96). Oropharyngeal symptoms were equally frequent in both groups. No dysphagia or other signs of eosinophilic oesophagitis occurred. Digestive adverse events (AE) were more frequent in the treated group ( P  = .02), but mild and without compliance issues. Only one severe advent event led to withdrawal in a patient who ingested twice the investigated treatment. Peanut‐specific humoral immune responses were modulated. Conclusion: The GIDOIT protocol demonstrated clinical and immunological efficacy and had an acceptable level of safety with weak oropharyngeal symptoms, no dysphagia, mild digestive events and few severe systemic AE.